Synthesis and optimization of a reactive oxygen species responsive cellular delivery system. (23rd February 2017) - Perez-Lopez, Ana M.; Valero, Elsa; Bradley, Mark
Abstract : Reactive oxygen species responsive delivery systems for the detection of peroxides in live macrophages have been designed. The oxidative cleavage of a boronic ester to a phenol triggered by hydrogen peroxide followed by self-immolation of a ROS-sensitive cleavable linker via 1, 6-elimination allowed the disturbance of the fluorescence resonance energy transfer turning on the near-infrared fluorescence. Abstract : Reactive oxygen species play numerous roles in a number of pathological processes. Monitoring H2 O2 is a powerful tool for imaging and therapy of diseases wherein oxidative stress is involved. In particular, we report a specific application of functional microspheres as sensors of H2 O2 . Reactive oxygen species responsive delivery systems were developed to detect in vitro peroxides thanks to the presence of a boronic ester which is readily cleaved with H2 O2 . This ROS-sensitive cleavable linker underwent a 1, 6-elimination to disrupt fluorescence resonance energy transfer by coupled near-infrared fluorophores such as Cy5.5/Cy7. This technology would allow real-time monitoring of therapeutic regimes (and their success), as well as optical detection of inflammation.